EFFECTIVE FACTORS ON SOUVENIR PURCHASE: THE CASE OF FOREIGN TOURISTS’ VIEWPOINT IN TEHRAN CITY - Vasheghani-Farahani, Farzaneh; Esfandiar, Kourosh; Tajzadeh-Namin, Abolfazl (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2014)
The present research aims to gain a better understanding of determinants on the souvenir-purchase behavior of inbound tourists, a vital factor affecting tourists’ experience in destinations, yet scant attention has been devoted to this in the literature. Drawing on the OH’s travel expenditure model (2007), this study examines the influence of three types of variables: individual traveler characteristics; trip characteristics; and the perceived value of the souvenirs on tourists’ spending on shopping. The results obtained, through an analysis of self-administered questionnaires gathered from a sample of 115 inbound tourists in Tehran city, showed that men tent to spend more on souvenir purchase than women; there is not a significant relationship in terms of shopping spending patterns between leisure tourists and business tourists; and design, traditional motifs, quality and portability of souvenirs affect purchase behavior considerably. Further analysis and other findings are also discussed, and recommendations for future research are put forth in this paper.